Cultural Change and Liberation in a Christian Perspective - Dumais, Marcel ((InCulturation. Working Papers on Living Faith and Culture), 1987)
Contiene varios ensayos de antropología y religión sobre el tema de cambio cultural y liberación en una perspectiva cristiana. Artículos y autores: "The Church of the Apostles: A Model of Inculturation?" por Marcel Dumais, p.1; "The Experience of Women in the Midst of Cultural Change", p.25; "Moral Polarization of Cultures", p. 47.